Knowledge Science, Engineering and Management : 11th International Conference, KSEM 2018, Changchun, China, August 17–19, 2018, Proceedings, Part II /: 11th International Conference, KSEM 2018, Changchun, China, August 17–19, 2018, Proceedings, Part II. (2018) - Unknown
No abstract available